Can Access to Spirometry in Asthma Education Centres Influence the Referral Rate by Primary Physicians for Education? - M Labrecque; M Lavallée; MF Beauchesne; A Cartier; LP Boulet (Canadian Respiratory Journal)
BACKGROUND AND OBJECTIVES: Asthma remains uncontrolled in a large number of asthmatic patients. Recent surveys have shown that a minority of asthmatic patients are referred to asthma educators. The objective of the present study was to assess the influence of increased access to spirometry in asthma education centres (AECs) on the rate of patient referrals to these centres by general practitioners.